Inflammatory markers and organ dysfunction in patients with severe influenza A (H1N1) virus-associated pneumonia - А. V. Malyarchikov; K. G. Shapovalov; E. I. Morozova; S. A. Lukyanov; L. S. Kazantseva (Фундаментальная и клиническая медицина)
Aim. To assess inflammatory markers and organ dysfunction in patients with severe influenza A (H1N1) virus-associated pneumonia.Materials and Methods. The study included 50 patients (median age 47 (38-62) years, 24 males and 26 females) with severe influenza A (H1N1) virus-associated pneumonia. We analysed the clinicopathological data as well as complete blood count and biochemical profile. Organ dysfunction was assessed using SOFA and qSOFA scales.Results. The prevalence of multiple organ dysfunction syndrome in patients with severe influenza A (H1N1) virus-associated pneumonia was 46% (23/50 patients). Patients frequently suffered from insufficient oxygenation, impaired coagulation, altered haemodynamics, and central nervous system dysfunction. Out of 23 patients with multiple organ dysfunction syndrome, 10 (43.5%) suffered from reduced oxygenation and excessive coagulation, while 6 (26.0%) had all mentioned syndromes combined. Thrombocytopenia was detected as early as at day 1-2 of the disease and was further accompanied by an increase in the erythrocyte sedimentation rate and white blood cell count from day 2 to day 8. An increase in acute-phase proteins (C-reactive protein and fibrinogen) was noted at the day 5-6 of the disease.Conclusion. In patients with severe influenza A (H1N1) virus-associated pneumonia, an early systemic inflammatory response evolves into an uncontrolled multiple organ dysfunction syndrome by day 7-8 of infection.